Angiopoietin-2 expression and its relationship with lymphangiogenesis and clinicopathological characteristics in cutaneous malignant melanoma - Zheng, Wei; Ju, Wei; Yang, Xi-Hu; Yan, Zhi-Xin (Frontiers in Oncology, 2023)
Objective: To investigate angiopoietin-2 (Ang-2/ANGPT2) expression and its relationship with lymphangiogenesis and clinicopathological characteristics in cutaneous malignant melanoma (CMM). Methods: Analysis gene expression difference in 472 patients between metastatic melanoma and melanoma in situ by TCGA database. And the target gene Ang-2 was screened. A clinical study was conducted to analyze the correlation between Ang-2 expression in CMM and tumor-associated lymphangiogenesis. Total of 42 patients with primary CMM who underwent extended tumor resection procedures at Affiliated Hospital of Jiangsu University were included in this study. Clinical data were collected. The expressions of both Ang-2 and LYVE-1 were detected by IHC. Lymphatic vascular density (LVD) was counted by using LYVE-1 to label lymphatic endothelial cells tumoral areas. Statistical analysis was used by Pearson correlation test and Student’s t-test. Results: The gene expression level of Ang-2 in 368 cases of metastatic melanoma was found significantly higher than that in 104 cases of melanoma in situ by searching the TCGA database. Correlation analysis showed a significant relationship between Ang-2 and LYVE-1/ VEGFR3 expression in CMM, and optimal cut-off value of survival analysis showed that high Ang-2 expression in CMM had a worse prognosis, based on TCGA database. Our research showed that Ang-2 was highly expressed in lymph node metastasis group and in the stage 3C-4 patients group than its expression in the group of patients with none lymph node metastasis and in the group of stage 0-3B patients, respectively. Our research also showed that LVD in the group of patients with lymph node metastasis and in the group of stage 3C-4 patients were significantly higher than that in the group of patients with none lymph node metastasis and in the group of Stage 0-3B patients, respectively. Breslow thickness also correlated with Ang-2 expression and LVD as well. Ang-2 expression and LVD were no relationship with gender and age. Ang-2 expression was obviously correlated with LVD. Conclusions: Evaluation of Ang-2 expression and LVD can be used to predict the risk of tumor lymphatic metastasis and to determine the prognosis of CMM. These results also may provide a new clinical treatment strategy for CMM.